A putative autonomous 20.5 kb-CACTA transposon insertion in an F3'H allele identifies a new CACTA transposon subfamily in Glycine max - Vodkin Lila; Zabala Gracia (BMC Plant Biology, 2008)
Abstract Background The molecular organization of very few genetically defined CACTA transposon systems have been characterized thoroughly as those of Spm/En in maize, Tam1 of Antirrhinum majus Candystripe1 (Cs1) from Sorghum bicolor and CAC1 from Arabidopsis thaliana, for example. To date, only defective deletion derivatives of CACTA elements have been described for soybean, an economically important plant species whose genome sequence will be completed in 2008. Results We identified a 20.5 kb insertion in a soybean flavonoid 3'-hydroxylase (F3'H) gene representing the t* allele (stable gray trichome color) whose origin traces to a single mutable chimeric plant displaying both tawny and gray trichomes. This 20.5 kb insertion has the molecular structure of a putative autonomous transposon of the CACTA family, designated Tgmt*. It encodes a large gene that was expressed in two sister isolines (T* and tm) of the stable gray line (t*) from which Tgmt* was isolated. RT-PCR derived cDNAs uncovered the structure of a large precursor mRNA as well as alternatively spliced transcripts reminiscent of the TNPA-mRNA generated by the En-1 element of maize but without sequence similarity to the maize TNPA. The larger mRNA encodes a transposase with a tnp2 and TNP1-transposase family domains. Because the two soybean lines expressing Tgmt* were derived from the same mutable chimeric plant that created the stable gray trichome t* allele line from which the element was isolated, Tgmt* has the potential to be an autonomous element that was rapidly inactivated in the stable gray trichome t* line. Comparison of Tgmt* to previously described Tgm elements demonstrated that two subtypes of CACTA transposon families exist in soybean based on divergence of their characteristic subterminal repeated motifs and their transposases. In addition, we report the sequence and annotation of a BAC clone containing the F3'H gene (T locus) which was interrupted by the novel Tgmt* element in the gray trichome allele t*. Conclusion The molecular characterization of a 20.5 kb insertion in the flavonoid 3'-hydroxylase (F3'H) gene of a soybean gray pubescence allele (t*) identified the structure of a CACTA transposon designated Tgmt*. Besides the terminal inverted repeats and subterminal repeated motifs,Tgmt* encoded a large gene with two putative functions that are required for excision and transposition of a CACTA element, a transposase and the DNA binding protein known to associate to the subterminal repeated motifs. The degree of dissimilarity between Tgmt* transposase and subterminal repeated motifs with those of previously characterized defective CACTA elements (Tgm1-7) were evidence of the existence of two subfamilies of CACTA transposons in soybean, an observation not previously reported in other plants. In addition, our analyses of a genetically active and potentially autonomous element sheds light on the complete structure of a soybean element that is useful for annotation of the repetitive fraction of the soybean genome sequence and may prove useful for transposon tagging or transposon display experiments in different genetic lines.